The effect of residential ecosystem zone with stunting event in Kupang - Joice Deby Nafi (Berita Kedokteran Masyarakat (BKM), 2018)
Stunting in children was one of malnutrition due to the limitations of overall socioeconomic conditions in the past. As a height, stunting was indexed by the age of less than minus two standard deviations (<-2 SD) or height of children under five was shorter than should be achieved at a certain age (Kemenkes 2010). Based on Riskesdas in 2013, the incidence of stunting in Indonesia tends to increase. The prevalence of under-fives stunting in 2013 was 37.2%. It was higher than in 2010 at 35.6%. The prevalence of stunting in East Nusa Tenggara was the highest nationally by 58.4% in 2010 and 51.7% in 2013 while in Kupang district the stunting incidence was still around 46.3% (Kemenkes 2013). The aims of this study were on determine the effect of residential ecosystem zone on the occurrence of stunting. Based on the results of the study, it conducted on 132 subjects spread in the highlands and low, known that environmental sanitation, intake of energid an infectious disease in fact be the determining factor of stunting events in children. The hilly area of NTT took care of the availability of food and health services. People in upland areas had more difficult access to health services, access to information, and the availability of primary needs than lowland communities. Poor people were faced with the fact that infrastructure does not support so they cannot obtain optimal health services. Communities were very limited with information about health and are further aggravated by cultural practices that do not support a healthy lifestyle. Stunting problems would cause problems in the future, if it was not handled early. It because of stunting not only inhibits physical growth alone, but also affected the mental and intelligence of children who could lead to poverty. Therefore, the stunting problem must get a quick intervention in order to save the nation's grater.